(3GdQSGdI GdOGeZI hGdMLI GdHGdZIs - (3jMji Hf MSf Hf ehSi GdbQTjs ((3MSf Hf eMeO Hf eMQe GdTQai s)
(3ChdgG (B:s
(3CfJ JgOi Edi GdHOQ GdedGeG hJSfO ef GdHMQ GdNUGeG s
(3BNQgG (B:s
(3hSjYde GdcGaQ def YbHi GdOGQ Je Pdc , hGddg CSCd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJs
(3bUjOI LhGHkG Ydi dSGf CejQ GdeDefjf GdfGUQ dOjf Gddg eMeO Hf CejQ GdeDefjf Edi SdWGf Gdjef GdCTQGa Yf bUjOg dg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs